Within-class consensus on classroom goal structures - Relations to achievement and achievement goals in mathematics and language classes - Bardach, Lisa; Yanagida, Takuya; Schober, Barbara; Lüftenegger, Marko (Learning and individual differences, 2018)
In the present study, we investigated students' shared perceptions, i.e., within-class consensus, on classroom goal structures, and how within-class consensus is related to achievement and achievement goals in mathematics and language classes. Within-class consensus was assessed for six dimensions of mastery goal structures, namely task, autonomy, recognition, grouping, evaluation, and time. Drawing on a sample of 1080 Austrian secondary school students enrolled in mathematics (22 classes) and language classes (24 classes), we estimated the effects of consensus on the outcome variables in multilevel models. The results indicated that achievement was positively predicted by consensus on evaluation in both subjects and by consensus on recognition in mathematics. Furthermore, in both subjects, consensus on recognition and evaluation negatively predicted performance-approach and performance-avoidance goals, and consensus on time negatively predicted performance-avoidance goals. Additionally, in mathematics classes, consensus on time negatively predicted performance-approach goals and consensus on task negatively predicted performance-avoidance goals. No relations between consensus and mastery goals were found in either subject. •Consensus on six classroom goal structures dimensions was investigated.•Separate analyses were conducted for mathematics and language classes.•In both domains, consensus on the evaluation dimension increased achievement.•Consensus on several dimensions decreased performance goals in both domains.•Consensus on classroom goal structures should be considered a substantive construct.